1992
DOI: 10.1002/pro.5560011104
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and vibrational spectroscopy of the cytochrome c: Cytochrome c oxidase complexes from bovine and Paracoccus denitrificans

Abstract: The 1: 1 complex between horse heart cytochrome c and bovine cytochrome c oxidase, and between yeast cytochrome c and Paracoccus denitrificans cytochrome c oxidase have been studied by a combination of second derivative absorption, circular dichroism (CD), and resonance Raman spectroscopy. The second derivative absorption and CD spectra reveal changes in the electronic transitions of cytochrome a upon complex formation. These results could reflect changes in ground state heme structure or changes in the protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
14
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 20 publications
6
14
0
Order By: Relevance
“…With regard to the effects of red light on the mitochondrial electron chain observed in this work, it is reasonable to surmise that this could be explained by the direct action of red light on mitochondrial photosensitizers (reviewed in Yeste et al, 2018). Indeed, we observed that red light affected the activity of CCO, which is a crucial component of the mitochondrial electron chain and is sensitive to light at a wavelength ranging from 630 to 660 nm (Lynch and Copeland, 1992). These observed FIGURE 8 | Effects of light-stimulation on cytochrome C oxidase activity in the presence/absence of either oligomycin A (Omy A) or FCCP.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…With regard to the effects of red light on the mitochondrial electron chain observed in this work, it is reasonable to surmise that this could be explained by the direct action of red light on mitochondrial photosensitizers (reviewed in Yeste et al, 2018). Indeed, we observed that red light affected the activity of CCO, which is a crucial component of the mitochondrial electron chain and is sensitive to light at a wavelength ranging from 630 to 660 nm (Lynch and Copeland, 1992). These observed FIGURE 8 | Effects of light-stimulation on cytochrome C oxidase activity in the presence/absence of either oligomycin A (Omy A) or FCCP.…”
Section: Discussionsupporting
confidence: 50%
“…Motile sperm subpopulations were determined through the protocol described in Luna et al (2017). In brief, individual kinematic parameters (VCL, VSL, VAP, LIN, STR, WOB, ALH, and BCF) recorded for each sperm cell were used as independent variables in a Principal Component Analysis (PCA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toward this end, we have introduced the use of second derivative absorption spectroscopy as a means of resolving and studying the individual electronic transitions of the 2 heme groups within the protein (Copeland, 1991(Copeland, , 1993Ishibe et al, 1991;Sherman et al, 1991;Lynch & Copeland, 1992;Lynch et al, 1992). During the course of these studies we have discovered a new electronic transition of one of the hemes at ca.…”
Section: J S Felsch Et Aimentioning
confidence: 99%
“…We have previously shown that the double Soret transition of ferrocytochrome a collapses to a single band at 443 nm when ferrocytochrome c is bound to the enzyme at the CU, site of subunit I1 (Lynch & Copeland, 1992;Lynch et al, 1992). Li et al (1988) and Nilsson et al (1988) have shown that mild heat treatment of the bovine enzyme selectively disrupts the structure around CU,.…”
mentioning
confidence: 97%